Effects of Drying Treatments on the Physicochemical Characteristics and Antioxidant Properties of the Edible Wild Mushroom Cyttaria espinosae Lloyd (Digüeñe Mushroom) - Marcelo Villalobos-Pezos; Ociel Muñoz Fariña; Kong Shun Ah-Hen; María-Fernanda Garrido Figueroa; Olga García Figueroa; Alexandra González Esparza; Luisbel González Pérez de Medina; José Miguel Bastías Montes (Journal of Fungi)
The wild mushroom Cyttaria espinosae, also known as digüeñe, is a parasitic ascomycete of Nothofagus trees endemic to southern Chile. This species of wild mushroom is of great nutritional importance, especially for the Mapuche indigenous communities, and is highly sought after. Edible wild mushrooms, rich in bioactive compounds, are a potential source of health-promoting components. In the case of C. espinosae, research on its bioactive compounds is still lacking as is research, on the effect of preservation treatments on these compounds due to its perishability. This study evaluates the effects of three drying treatments; freeze-drying, hot-air drying, and microwave–vacuum drying. The rehydration capacity, color, and microstructural properties of dried mushrooms were evaluated using SEM, while, total phenolic content, antioxidant activity determined by DPPH and ORAC assays, and ergothioneine levels were investigated in both fresh and dried extracts of C. espinosae. The results showed that freeze-drying and microwave–vacuum drying are recommended treatments for the digüeñe mushroom due to superior outcomes in rehydration rate, color, and structural properties observed through SEM images. Total phenolic content and antioxidant activity were higher in mushroom extracts dried by microwave–vacuum compared to the other drying treatments.